Analisis Sentimen Publik Mengenai Kebijakan Penggunaan Hp Di Bawah Umur Melalui Hastag #Pptunas - Farida Hayati; Basma Fathimah; Syakira Azzahra; Verrel Nathanael; Wedly Junanda Situmorang; Raja Rafli Putra Samudra; Novaria Maulina; Yuanita Setyastuti (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2026)
This study aims to analyze public sentiment toward the PP Tunas policy regarding child protection in digital spaces through the hashtag #PPTunas on social media. The research employed a descriptive qualitative method with a netnographic approach. Data were collected using Brand24 from conversations on X and TikTok during March - April 2026. The findings show that positive sentiment dominated at 59%, while negative sentiment reached 41%. Positive sentiment was mainly driven by official institutions and mass media that framed support for the policy. In contrast, negative sentiment emerged from personal accounts highlighting concerns about privacy, digital surveillance, and the importance of digital literacy for children and parents. The study indicates that public opinion regarding PP Tunas is strongly influenced by media roles and government communication strategies in shaping perceptions within digital spaces.